Educating to the gift - Gramigna, Anita (Historia y Memoria de la Educación, 2016)
With an educational goal in mind, this work reconstructs a trail of personal studies stretching from the eighties to the present day. The underlying premise is that the theory of the Gift of Marcel Mauss, in particular in Ricoeur’s reworking when he intersects it with the theme of recognition, opens significant educational perspectives. Practicing generosity towards others, as well as acknowledging and reciprocating it, implies, regardless of any markets logic, a path of cultural enrichment and of the universally shared meaning of life’s dignity. This has to do not only with the cognitive approach to difference, but also with a moral commitment that recognizes the depth of values when they are directed towards the practice of rights. The epistemological framework of the analysis is, in accordance with Ricoeur’s lesson, hermeneutic; the methodology, intended here as a normative epistemology, is of a qualitative kind.